The commodification and exploitation of fresh water: Property, human rights and green criminology. (March 2016) - Johnson, Hope; South, Nigel; Walters, Reece
Abstract: In recent years, both developing and industrialised societies have experienced riots and civil unrest over the corporate exploitation of fresh water. Water conflicts increase as water scarcity rises and the unsustainable use of fresh water will continue to have profound implications for sustainable development and the realisation of human rights. Rather than states adopting more costly water conservation strategies or implementing efficient water technologies, corporations are exploiting natural resources in what has been described as the "privatization of water". By using legal doctrines, states and corporations construct fresh water sources as something that can be owned or leased. For some regions, the privatization of water has enabled corporations and corrupt states to exploit a fundamental human right. Arguing that such matters are of relevance to criminology, which should be concerned with fundamental environmental and human rights, this article adopts a green criminological perspective and draws upon Treadmill of Production theory.